Hubungan Karakteristik Ibu dan Jarak Pelayanan Kesehatan Dengan Kelengkapan Imunisasi Dasar di Puskesmas Dulukapa - Libunelo, Elvi; Paramata, Yeni; Rahmawati, Rahmawati (Universitas Gorontalo, 2018)
Every year more than 1.4 million children in the world die from variousdiseases that can be prevented by immunization. The purpose of thisresearch was to know the relationship of mother characteristic anddistance of health service to the completeness of basic immunization ininfant in Dulukapa.The type of the study was an analytic survey usingcross sectional study design, sampling technique ie exhautive samplingwhich was a sampling scheme where the researcher token all thesubjects from the population as the samples as many as 150 babies.The analysis was used univariate and bivariate analysis with chisquare test. The proportion of infants who received completeimmunization 92 (61.3%) infants and immunizations did not complete asmany as 58 (38.7%) babies. Using the chi square statistical test showedthat there was significant associated between maternal education (pvalue = 0.002), maternal occupation (p value = 0,000), maternalknowledge (p value = 0,000), health service distance (р value = 0,002)with completeness of immunization base on the baby. To improve thecompleteness of basic immunization in infants, the mother should payattention to infant health and always bring the baby to the immunizationand to the health center and health personnel to further improve healtheducation routinely, especially in the provision of basic immunization.